Financial Stress, Dampak dan Strategi Penanganannya Pada Mahasiswa Selama Studi - Anfas, Anfas; Syamsuddin, Fajar Rakasiwi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This research systematically reviews the factors influencing student financial stress, its impact on academic success, and effective coping strategies. A literature review of studies published between 2020 and 2025 reveals that student financial stress results from the interaction of personal factors (literacy, self-efficacy, attitude towards debt), structural factors (cost of education and economic conditions), and situational factors (the pandemic and social pressure). The reported impacts encompass mental health, academic motivation, and general well-being. Mitigation efforts require a holistic approach combining financial education, psychological support, and institutional policies to foster a learning environment that is financially and emotionally healthier. This review contributes to enriching the understanding of the importance of student financial well-being for long-term academic success.